PPV Criterion of a Rock Slope Imbedded with a Fault subjected to Blasting P-Waves - Shiwei Lu; Chuanbo Zhou; Zhen Zhang; Ling Ji; Nan Jiang (Shock and Vibration)
The open-pit mining slopes continue to become higher and steeper with the continuous exploitation of near-surface mineral resources. The blasting excavation exerts a significance influence on the slope stability. In fact, intact rock slopes do not exist and slope stability is controlled by the geological defects. In this paper, the stability of a rock slope imbedded with a fault is considered. The P-wave component of blasting seismic waves is focused on and the fault is simplified as a semi-infinite crack. In background of Daye iron mine, the peak particle velocity (PPV) threshold is determined based on the linear elastic fracture dynamics. The influence of frequency, Young's modulus, and Poisson's ratio is studied to modify the PPV threshold. Results show that (1) the PPV threshold decreases with the increasing Young's modulus and Poisson's ratio, but increases with the increasing frequency; (2) the initiation angle is immune to Young's modulus and the frequency, and only depends on the Poisson's ratio; (3) the PPV criterion is finally determined as 1.47 cm/s when the frequency f ≤ 10 Hz, 1.47 cm/s–3.30 cm/s when 10 Hz < f ≤ 50 Hz and 3.37 cm/s–6.59 cm/s when f > 50 Hz, which are far less than that of intact rock slopes; (4) The north slope is quite safe if the proposed PPV threshold is not violated due to the variation range of the initiation angle θ0.